Successful maternal and fetal outcome in a patient with chronic myeloid leukemia on chemotherapy - Jaiswal, Nishtha; Khullar, Harsha; Mediratta, Geeta; Garg, Sharmistha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Chronic myeloid leukemia (CML) is a myeloproliferative-neoplasm accounting for 15% of adult leukemias. Management of leukemia in pregnancy and effect of anti-neoplastic agents on pregnancy outcomes is not well investigated. Management of pregnancy in CML is complicated by the fact that drug used in its treatment i.e. imatinib can lead to teratogenicity in fetus, whereas withholding the drug may lead to relapse of disease. However, pregnancy itself does not alter course of CML. A 19-year-old female, was diagnosed with CML at 15 years of age. She was positive for Philadelphia chromosome. She was on imatinib and had achieved clinical, hematologic and molecular remission. Patient was on regular follow-up till 18 years of age. 45 months post diagnosis she presented with 8 weeks amenorrhoea. Ultrasound (USG) done at 5 weeks gestation showed a single live intrauterine fetus. She took imatinib during this period of organogenesis, so she was advised medical termination of pregnancy (MTP) by treating oncologist. However, patient denied MTP, so her imatinib was stopped and pregnancy continued. The quantitative Bcr/Abl PCR transcript levels at 16, 20 and 28 weeks of gestation were not detectable. The patient did not develop any symptoms or signs suggestive of CML and total leucocyte count remained normal throughout pregnancy. Patient went into preterm-labor at 36 weeks gestation and delivered a healthy male baby weighing 3.1 kg. The baby was well and had a normal examination. USG abdomen of baby was also normal. CML in pregnancy is rare and imatinib is the drug of choice with which long term survival is possible. Imatinib in large case series has been known to be associated with adverse fetal outcomes although evidence to the contrary also exists. Further studies are needed to draw a conclusion on this debatable issue.